A educação ambiental na bacia hidrográfica do rio do Cabelo, João Pessoa-PB : uma análise da degradação e da percepção dos discentes de uma escola do baixo curso do rio - Santos, Joel Carneiro dos (2005)
This is a research about the Environmental Education in the Hydrographical Basin of Cabelo River, João Pessoa PB: an analysis of the degradation and the students perception of a school in the low flow of the river. It is based on the project of the CEFET-PB Natural Researches Technical Course in the Hydrographical Basin of Cabelo River and in the Mata Atlântica/ Cabelo river project. In an exploratory research as part of the projects, it was detected, in all the extension of the water flow, an intensive degradation process mainly in the low flow in stretches like the Ponte River, called this way by the community, and in the mouth of the river. In both of them, after the water analysis in the CEFET-PB laboratories, a high level of pollution was detected. This water is widely used by the local community every day. These aspects were the reason why this place was used as a study source. It was chosen as a research object for being located close to the Municipal School Antônio Santos Coelho Neto. Groups from the 5th and 6th grades were selected both as research object and as sample, so that exposed to the Environmental Education process, they would be able to analyse the environmental problems in the location and stimulate their perceptions by building a pedagogic and methodological way to combat the growing degradation that affects that hydrographical basin. The methodology chosen for the development of the investigation was structured by the following phases: exploratory, that consists of an analysis of reality; systematisation phase of the data and planning of the actions; intervention phase followed by the analysis and discussion of the results. The research data were obtained through the methodological procedures with practices involving games, voluntary rubbish collection, tracks, sensitiveness by using music, visualization of the vegetation for conservation practices, questionnaires and demonstrative graphics. The results have showed that the local school community studied is aware of the environmental problems caused by atrophic actions in the whole flow of the river. According to the students, the community and the visitors in the area are the main polluters with rubbish, sewage and several wastes. In a major part of the answers to the questionnaires, education was referred to, by the students, as a solution for the pollution problem in Cabelo river, what emphasizes the willingness for a continuous Environmental Education program in the community, having the students as multiplier agents.